2021
DOI: 10.1080/03057267.2021.1963579
|View full text |Cite
|
Sign up to set email alerts
|

Towards a better understanding of conceptual difficulties in introductory quantum physics courses

Abstract: Research on teaching and learning quantum physics (QP) frequently explores students' conceptual difficulties to identify common patterns in their reasoning. The abstractness of QP is often found to be at the origin of students' conceptual difficulties. Due to this abstract nature students resort to common sense reasoning or classical thinking when they make meaning of QP phenomena. In this literature review, the 'abstractness' is closely investigated and nuanced to uncover what reasons for the abstractness stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 88 publications
3
41
0
Order By: Relevance
“…At the same time, quantum physics can be challenging for both teachers and students. A recent review by Bouchée et al (2021) identified four reasons for students' conceptual difficulties in quantum physics. These are struggles (a) to relate the mathematical formalism to experiences in the physical world; (b) to interpret counter-intuitive phenomena and concepts; (c) to transit from a deterministic to a probabilistic world view; and (d) to understand the limitations of language to express quantum phenomena, concepts, and objects.…”
Section: Quantum Physics and Its Place In Educationmentioning
confidence: 99%
See 4 more Smart Citations
“…At the same time, quantum physics can be challenging for both teachers and students. A recent review by Bouchée et al (2021) identified four reasons for students' conceptual difficulties in quantum physics. These are struggles (a) to relate the mathematical formalism to experiences in the physical world; (b) to interpret counter-intuitive phenomena and concepts; (c) to transit from a deterministic to a probabilistic world view; and (d) to understand the limitations of language to express quantum phenomena, concepts, and objects.…”
Section: Quantum Physics and Its Place In Educationmentioning
confidence: 99%
“…It is thus important to develop and evaluate teaching strategies that help students overcome the challenges above and develop quantum understanding. Although these issues have been discussed in physics education research for more than 20 years (see, e.g., Zollman, 1999), they are still prevalent (Bungum et al, 2018;Krijtenburg-Lewerissa et al, 2017;Bouchée et al, 2021). Among challenging topics in quantum physics is wave-particle duality, identified as a key topic by experts in a Delphi study by Krijtenburg-Lewerissa et al (2019).…”
Section: Quantum Physics and Its Place In Educationmentioning
confidence: 99%
See 3 more Smart Citations